О биомеханике жевания землероек - Михалевич, О.А.; Гайченко, В.А. (Вестник зоологии, 1976)
Having studied the simplest mathematical model of the chewing act in shrews, the authors advanced a supposition on the dependence of the press force of the mandible on its dimensions and inclination angle of the ascending branch. A formula is presented, which will be of use when determining an approximate length of the mandible, height of the ascending branch and inclination angle of the coronoid process from the fragmentary material.